Factor Analysis of Rural Consumers’ Preference Attributes in the Purchase of Cell Phone : An Empirical Analysis - Sureshrajan, S. G.; Selvachandra, M. (Prabandhan: Indian Journal of Management, 2011)
Cell Phone industry continues to grow at the rate of 15% - 20% year on year. A key factor contributing to this growth, is the rural consumers’ potential, because the rural market is zooming ahead at around 25 percent annually based on the rural consumers’ socio-economic changes (lifestyle, habits and tastes, economic status), literacy level, infrastructure facilities, increase in income, increase in expectations etc. This study focuses on rural consumers’ preference attributes at the time of purchase of Cell Phone.